Spherical alumina powder, resin composition, heat dissipation material

JP7639019B2Active Publication Date: 2025-03-04DENKA CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022553908
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-29
Filing Date
2021-09-24
Publication Date
2025-03-04
Estimated Expiration
2041-09-24

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、良好な流動性を示し実用的な球状アルミナ粉末を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639019000002
    Figure 0007639019000002
  • Figure 0007639019000001
    Figure 0007639019000001
Patent Text Reader

Abstract

The present invention provides a spherical alumina powder which is configured such that: in the particle size distribution thereof as measured by a laser diffraction / scattering particle size distribution measuring device, the maximum particle diameter indicating the maximum peak is within the range of from 35 μm to 70 μm; the frequency of the maximum particle diameter is from 5% to 15%; and among the respective frequencies of 20 particle diameters obtained by dividing the particle diameter range of from 1 μm to 20 μm into 19 equal parts, the frequencies of at least 6 particle diameters are 0.1% or more, and the cumulative frequency of the particle diameter range of from 1 μm to 20 μm is from 3% by volume to 17% by volume.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spherical alumina powder, a resin composition, and a heat dissipating material. [Background technology]

[0002] In recent years, in response to the demand for smaller, lighter, and more powerful electronic devices, the miniaturization, thinning, and narrowing of semiconductor packages has been accelerating. In addition, the mounting method has become dominated by surface mounting, which is suitable for high-density mounting on wiring boards and the like. As such, as semiconductor packages and their mounting methods progress, there is a demand for improved performance in heat dissipation materials, and research has been actively conducted into highly loading ceramic powder, especially spherical alumina powder, into silicone resin. The problem with highly loading ceramic powder is that it increases the viscosity of the material, which increases defects in molding processing.

[0003] To solve this problem, improvements have been made from both the resin and the ceramic powder side. Improvements from the ceramic powder side include, for example, a method of increasing Wardle's sphericity to 0.7 to 1.0 (Patent Document 1), a method of broadening the particle size distribution by setting the gradient of the straight line shown in the Rosin-Rammler diagram to 0.6 to 0.95 (Patent Document 2), and a method of providing several peaks in the particle size distribution to make it multimodal, thereby bringing the ceramic powder closer to a close-packed structure (Patent Document 3). However, these improvements are still insufficient, and increasing the packing rate causes a sudden increase in the viscosity of the material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 3-066151 [Patent Document 2] Japanese Patent Application Publication No. 6-080863 [Patent Document 3] Japanese Patent Application Publication No. 8-003365 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in order to solve the above problems, and an object of the present invention is to provide a practical spherical alumina powder which exhibits good fluidity. [Means for solving the problem]

[0006] Means of the Invention The present inventors have conducted intensive research to solve the above problems, and as a result have found that the above problems can be solved by the present invention described below, thereby completing the present invention. That is, the present invention is as follows.

[0007] [1] A spherical alumina powder in which, in a particle size distribution measured using a laser diffraction / scattering particle size distribution analyzer, a maximum particle diameter showing a maximum peak is in the range of 35 to 70 μm, the frequency of said maximum particle diameter is 5 to 15%, and among the frequencies of 20 particle diameters divided into 19 equal parts in a particle diameter range of 1 to 20 μm, the frequencies of at least 6 particle diameters are 0.1% or more, and the cumulative value of the frequencies in the particle diameter range of 1 to 20 μm is 3 to 17 vol.%. [2] The spherical alumina powder according to [1], wherein the cumulative value of the frequency of particles having a particle size range of 20 to 100 μm in the range of the maximum peak is 70 volume % or more. [3] A resin composition comprising a resin and the alumina powder according to [1] or [2]. [4] A heat dissipation material comprising the resin composition according to [3]. Effect of the Invention

[0008] According to the present invention, it is possible to provide a practical spherical alumina powder which exhibits good fluidity. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a graph showing the particle size distribution of the spherical alumina powder of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the particle size distribution of the spherical alumina powder of the present invention, as measured by a laser diffraction / scattering type particle size distribution measuring device, the maximum particle size showing a maximum peak is in the range of 35 to 70 μm, the frequency of the maximum particle size is 6 to 12%, the frequency of at least 6 of the 20 particle size points divided into 19 equal parts in the particle size range of 1 to 20 μm is 0.1% or more, and the cumulative frequency of the particle size range of 1 to 20 μm is 3 to 17 volume %.

[0011] As described above, the present invention shows that the main component is a spherical alumina powder having a maximum peak, and spherical alumina powder having a smaller diameter than this spherical alumina powder is evenly present in the particle diameter range of 1 to 20 μm, thereby obtaining an even further improved fluidity effect than before.

[0012] The reason why the above-mentioned effect of improving the fluidity is obtained is presumed to be as follows. Usually, when the powder is densely packed, liquid bridges are formed between the particles due to the influence of moisture in the atmosphere. When liquid bridges are formed, the viscosity increases, and the fluidity decreases when the resin composition is made. In consideration of this phenomenon, in the present invention, it is presumed that by uniformly distributing the above-mentioned small-diameter spherical alumina powder having a particle diameter in the range of 1 to 20 μm, the liquid bridges formed between the particles of the spherical alumina powder having a maximum peak are suppressed, and high fluidity is exhibited even when the powder is in a dense state. Hereinafter, an embodiment of the present invention (the present embodiment) will be described in detail. [Spherical alumina powder] In the particle size distribution of the spherical alumina powder according to this embodiment, measured using a laser diffraction / scattering type particle size distribution measuring device, the maximum particle diameter showing the maximum peak is in the range of 35 to 70 μm, and the frequency of the maximum particle diameter is 5 to 15%. If the maximum particle size is outside the above range, the rolling resistance increases and the viscosity of the resin composition containing the spherical alumina powder increases.The maximum particle size is preferably in the range of 40 to 65 μm.

[0013] Furthermore, if the frequency of the maximum particle size is not within the range of 5 to 15%, the rolling resistance increases and the viscosity of the resin composition containing the spherical alumina powder increases. The frequency of the maximum particle size is preferably within the range of 7 to 11%.

[0014] Furthermore, in the spherical alumina powder according to this embodiment, among the frequencies of 20 particle diameters (20 particle diameters of 1 μm, 2 μm, 3 μm, ..., 20 μm) divided into 19 equal parts in the particle diameter range of 1 to 20 μm, the frequency of each of at least 6 particle diameters is 0.1% or more, and the cumulative value of the frequencies in the particle diameter range of 1 to 20 μm is 3 to 15 volume %. If this condition is not satisfied, the liquid crosslinking suppression effect is reduced, and the viscosity of the resin composition containing the spherical alumina powder increases. Of the 20 particle diameters, the frequency of each of 9 particle diameters is preferably 0.1% or more. In addition, the frequency is preferably 0.2% or more. The upper limit of the frequency is preferably about 2%. Furthermore, the cumulative value of the above frequency for particle sizes in the range of 1 to 20 μm is preferably 3 to 17% by volume.

[0015] As described above, the maximum peak is measured by a laser diffraction scattering type particle size distribution analyzer, but specifically, it can be measured and calculated by the method described in the Examples.

[0016] The cumulative frequency of the particle size range of 20 to 100 μm in the particle size region in the range of the maximum peak is preferably 70% by volume or more, more preferably 75 to 90% by volume. By having the cumulative frequency of 70% by volume or more, an increase in viscosity can be prevented.

[0017] Here, the range of the peak having the maximum peak refers to the range from a particle size of 20 μm through the maximum peak to the minimum frequency, preferably a particle size range of 20 to 100 μm. The diameter at which the frequency is maximum within the above range is the maximum particle size.

[0018] The average particle size of the spherical alumina powder according to this embodiment is preferably 35 to 70 μm, and more preferably 40 to 50 μm. By setting the average particle size to 35 to 70 μm, an increase in viscosity can be prevented. Here, the average particle size is a cumulative 50% diameter (D50) on a volume basis measured by a laser diffraction scattering type particle size distribution measuring device, and can be measured and calculated by the method described in the Examples.

[0019] The average sphericity of the spherical alumina powder according to this embodiment is preferably 0.9 or more, and more preferably 0.92 to 1. When the average sphericity is 0.9 or more, an increase in viscosity can be prevented. Here, the average sphericity can be measured and calculated by the method described in the Examples.

[0020] The specific surface area is 0.1 to 0.4 m 2 / g, and 0.2 to 0.3 m 2 More preferably, the specific surface area is 0.1 to 0.4 m / g. 2 / g, an increase in viscosity can be prevented. Here, the specific surface area is a value based on the BET method, and can be measured and calculated by the BET single point method.

[0021] The spherical alumina powder according to this embodiment can be produced, for example, as follows. First, the alumina raw material powder serving as the raw material is preferably an alumina powder or an aluminum hydroxide powder. Then, alumina raw material powder having an average particle diameter approximately the same as the desired maximum particle diameter is introduced into a high-temperature flame formed with a fuel gas such as hydrogen, natural gas, acetylene gas, propane gas, butane, or LPG, and melted and spheroidized to produce a first spherical alumina powder. Similarly, a second spherical alumina powder is prepared by melting and spheroidizing an alumina raw material powder having an average particle size of 1 to 20 μm. The average sphericity and specific surface area of ​​the spherical alumina powder can be adjusted by controlling at least one of the temperature inside the furnace in which the high-temperature flame is formed, the particle size of the alumina raw material powder, and the input amount.

[0022] Next, the particle size distribution of the first spherical alumina powder is adjusted to a desired range using a sieve or a precision air classifier, etc. Similarly, the particle size distribution of the second spherical alumina powder is adjusted to a desired range using a sieve or a precision air classifier, etc. The desired range in this case refers to a range in which the frequency of each of at least 6 particle diameters among 20 particle diameters divided into 19 equal parts in the particle diameter range of 1 to 20 μm is 0.1% or more, a range in which the maximum particle diameter showing the maximum peak is in the range of 35 to 70 μm and the frequency of the maximum particle diameter is 6 to 12%, etc. In addition, by adjusting the feed amount in precision air classification, the peak shape of the particle size distribution can be made sharper or broader.

[0023] [Resin composition, heat dissipation material] The resin composition according to the present invention contains a resin and the alumina powder according to the present invention described above. The heat dissipating material according to the present invention also contains the resin composition according to the present invention described above.

[0024] Examples of resins that can be used include silicone resin, epoxy resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyamide such as polyimide, polyamideimide, polyetherimide, polyester such as polybutylene terephthalate, polyethylene terephthalate, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, etc.

[0025] Among these, the resin for the heat dissipation material is preferably a silicone resin, and is preferably at least one of an addition reaction type silicone resin and a condensation reaction type silicone resin. If necessary, a part of the silicone resin may be replaced with a silicone rubber. The silicone rubber is preferably at least one of an addition reaction type silicone rubber and a peroxide vulcanization type silicone rubber. In any of these silicone resins and silicone rubbers, the average composition formula is 1 n SiO (4-n) / 2 (In the formula, R 1 are the same or different unsubstituted or substituted monovalent hydrocarbon groups, and n is a positive number of 1.98 to 2.02.

[0026] Specific examples of silicone resins include one-component silicones having both vinyl and H-Si groups in one molecule, and two-component silicones of organopolysiloxanes having vinyl groups at the end or side chains. Commercially available products include, for example, Toshiba Silicones, under the trade names "XE14-8530," "TSE-3062," and "YE5822."

[0027] The resin composition or heat dissipating material of the present invention may contain the following components as necessary: ​​Stress reducing agents include rubber-like substances such as silicone rubber, polysulfide rubber, acrylic rubber, butadiene rubber, styrene block copolymers, and saturated elastomers, various thermoplastic resins, and further resins obtained by modifying epoxy resins and phenolic resins in whole or in part with aminosilicone, epoxysilicone, alkoxysilicone, etc. Examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino silanes such as aminopropyltriethoxysilane, ureidopropyltriethoxysilane, phenylaminosilane and N-phenylaminopropyltrimethoxysilane; hydrophobic silane compounds such as phenyltrimethoxysilane, methyltrimethoxysilane and octadecyltrimethoxysilane; and mercaptosilanes. Examples of the surface treatment agent include Zr chelate, titanate coupling agent, and aluminum-based coupling agent. Examples of the flame retardant include halogenated epoxy resins and phosphorus compounds, and examples of the colorant include carbon black, iron oxide, dyes, and pigments. As a flame retardant assistant, Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 etc. Examples of the release agent include natural waxes, synthetic waxes, metal salts of linear fatty acids, acid amides, esters, and paraffin.

[0028] The content of the spherical alumina powder of the present invention in the resin composition or the heat dissipating material is preferably 50 to 95% by mass. By being in the above range, desired heat resistance, moldability, etc. can be obtained.

[0029] The resin composition or heat dissipating material of this embodiment can be produced by blending predetermined amounts of each of the above-mentioned materials using a blender, a Henschel mixer, or the like, kneading the mixture using a heated roll, a kneader, a single-screw or twin-screw extruder, or the like, cooling the mixture, and then appropriately pulverizing it.

[0030] Furthermore, when making the spherical alumina powder of the present invention into a resin composition or a heat dissipation material, the surface of the powder can be treated with the aforementioned silane coupling agent or the like to reduce the water absorption of the powder, increase the strength of the resin composition, and further reduce the interfacial resistance between the resin and the powder, thereby further improving the thermal conductivity.

[0031] The heat dissipating material according to this embodiment is preferably a thin molded product in the form of a sheet or the like, and the processing method thereof may be a conventionally known method, such as a doctor blade method, coating with a comma coater, an extrusion method, etc. The thickness of the sheet-shaped heat dissipating material is preferably 0.3 mm or more. EXAMPLES

[0032] The present invention will be described in more detail below using examples and comparative examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.

[0033] [Example 1] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 46 μm.

[0034] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm. The average particle size and average sphericity were measured as follows (the same applies to the following Examples and Comparative Examples).

[0035] (Method of measuring average particle size) The average particle size (volume basis) of the spherical alumina powder was measured by a laser diffraction scattering method (Microtrac (manufactured by Nikkiso, product name "MT3300EX II")).

[0036] (Method of measuring average sphericity) The average sphericity of spherical alumina powder was measured using a flow-type particle image analyzer, Sysmex Corporation, trade name "FPIA-3000", as follows. The projected area (A) and perimeter (PM) of the particle were measured from the particle image. If the area of ​​a perfect circle corresponding to the perimeter (PM) is taken as (B), the sphericity of the particle can be expressed as A / B. Assuming a perfect circle with the same perimeter as the perimeter (PM) of the sample particle, PM=2πr, B=πr 2 Therefore, B = π × (PM / 2π) 2 The sphericity of each particle is given by: Circularity = A / B = A × 4π / (PM) 2 This was measured for 100 or more randomly selected particles, and the average value was squared to obtain the average sphericity. The measurement solution was prepared by adding 20 ml of distilled water and 10 ml of propylene glycol to 0.1 g of sample, and subjecting the mixture to ultrasonic dispersion for 3 minutes.

[0037] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 5:95 to obtain the spherical alumina powder of Example 1 (average particle size: 45 μm, specific surface area: 0.2 m). 2 / g) was prepared. The particle size distribution (particle size and frequency) of the spherical alumina powder of Example 1 was measured by a laser diffraction scattering method. The above-mentioned Microtrac was used as a particle size distribution measuring device for the measurement. The results are shown in Table 1 below.

[0038] The spherical alumina powder thus prepared was added to a vinyl-containing polymethylsiloxane (manufactured by Momentive Performance Materials Japan, LLC, product name YE5822A Liquid) so that the resin composition contained 65% by volume (88.1% by mass), and then the mixture was stirred and degassed to prepare a resin composition for viscosity measurement. A B-type viscometer (manufactured by Toki Sangyo Co., Ltd., product name "TVB-10") was used to measure the viscosity at 30°C. The results are shown in Table 1. The viscosity is preferably 100 Pa·s or less.

[0039] [Example 2] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 45 μm.

[0040] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0041] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 15:85 to obtain spherical alumina powder of Example 2 (average particle size: 40 μm, specific surface area: 0.3 m). 2 / g) was prepared.

[0042] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0043] [Example 3] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 43 μm.

[0044] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0045] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 5:95 to obtain the spherical alumina powder of Example 3 (average particle size: 43 μm, specific surface area: 0.2 m). 2 / g) was prepared.

[0046] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0047] [Example 4] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 55 μm.

[0048] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 7 μm.

[0049] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 15:85 to obtain the spherical alumina powder of Example 4 (average particle size: 52 μm, specific surface area: 0.3 m). 2 1 shows the particle size distribution of the spherical alumina powder of Example 4.

[0050] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0051] [Example 5] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 38 μm.

[0052] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0053] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 15:85 to obtain the spherical alumina powder of Example 5 (average particle size: 36 μm, specific surface area: 0.2 m). 2 / g) was prepared.

[0054] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0055] [Example 6] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 57 μm.

[0056] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0057] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 5:95 to obtain the spherical alumina powder of Example 6 (average particle size: 55 μm, specific surface area: 0.2 m). 2 / g) was prepared.

[0058] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0059] [Example 7] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 50 μm.

[0060] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0061] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 10:90 to obtain the spherical alumina powder of Example 7 (average particle size: 44 μm, specific surface area: 0.2 m). 2 / g) was prepared.

[0062] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0063] [Example 8] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 57 μm.

[0064] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0065] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 20:80 to obtain the spherical alumina powder of Example 8 (average particle size: 52 μm, specific surface area: 0.2 m). 2 / g) was prepared.

[0066] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0067] [Comparative Example 1] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 55 μm.

[0068] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0069] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 20:80 to obtain the spherical alumina powder of Comparative Example 1 (average particle size: 50 μm, specific surface area: 0.2 m). 3 / g) was prepared.

[0070] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0071] [Comparative Example 2] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 46 μm.

[0072] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0073] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 2:98 to obtain spherical alumina powder of Comparative Example 2 (average particle size: 46 μm, specific surface area: 0.1 m). 3 / g) was prepared.

[0074] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0075] [Comparative Example 3] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 46 μm.

[0076] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0077] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 20:80 to obtain a spherical alumina powder of Comparative Example 3 (average particle size: 42 μm, specific surface area: 0.4 m). 3 / g) was prepared.

[0078] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0079] [Comparative Example 4] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 32 μm.

[0080] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0081] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 10:90 to obtain spherical alumina powder of Comparative Example 4 (average particle size: 30 μm, specific surface area: 0.3 m). 3 / g) was prepared.

[0082] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0083] [Comparative Example 5] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 61 μm.

[0084] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0085] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 5:95 to obtain a spherical alumina powder of Comparative Example 5 (average particle size: 60 μm, specific surface area: 0.2 m). 3 / g) was prepared.

[0086] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0087] [Comparative Example 6] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 45 μm.

[0088] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 5 μm.

[0089] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 15:85 to obtain a spherical alumina powder of Comparative Example 6 (average particle size: 43 μm, specific surface area: 0.2 m). 2 / g) was prepared.

[0090] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0091] [Comparative Example 7] (Preparation of first spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 47 μm.

[0092] (Preparation of second spherical alumina powder) Alumina powder was introduced into a flame formed by LPG and oxygen gas, and the powder was subjected to a spheroidizing process. After that, the powder was classified by cyclone classification to obtain alumina powder with an average sphericity of 0.92 and an average particle size of 10 μm.

[0093] The first spherical alumina powder and the second spherical alumina powder were mixed in a volume ratio of 15:85 to obtain spherical alumina powder of Comparative Example 7 (average particle size: 45 μm, specific surface area: 0.2 m). 3 / g) was prepared.

[0094] Using the spherical alumina powder, a resin composition was prepared in the same manner as in Example 1, and the viscosity of the prepared resin composition was measured. The results are shown in Table 1 below.

[0095] [Table 1] [Industrial Applicability]

[0096] The spherical alumina powder of the present invention is preferably used as a filler for a thermally conductive resin composition. The resin composition of the present invention is also used as a heat dissipation member for heat countermeasures in personal computers, automobiles, portable electronic devices, household electrical appliances, etc.

Claims

1. In a particle size distribution measured by a laser diffraction / scattering particle size distribution measuring device, a maximum particle size showing a maximum peak is in the range of 35 to 70 μm, and the frequency of the maximum particle size is 5 to 15%, A spherical alumina powder in which, among the frequencies of 20 particle diameters divided into 19 equal parts in the particle diameter range of 1 to 20 μm, the frequencies of at least 6 particle diameters are 0.1% or more, and the cumulative value of the frequencies in the particle diameter range of 1 to 20 μm is 3 to 17 volume % (excluding alumina having a unimodal particle size distribution with only one maximum value, which is 2.69 [%], and the particle size giving the maximum value is 52 μm).

2. 2. The spherical alumina powder according to claim 1, wherein the cumulative frequency of particles in the particle size range of 20 to 100 μm in the range of the maximum peak is 70% by volume or more.

3. A resin composition comprising a resin and the alumina powder according to claim 1 or 2.

4. A heat dissipating material comprising the resin composition according to claim 3.

Citation Information

Patent Citations

  • Semiconductor device

    JP1991066151A

  • Epoxy resin composition

    JP1994080863A

  • Resin composition for molding

    JP1996003365A

  • Highly thermally conductive inorganic powder and resin composition compounded therewith

    JP2004244491A

  • Surface modification method of inorganic oxide powder, powder prepared through the same, and its use

    JP2004262674A